LEGAL POSITIONS OF THE CONSTITUTIONAL COURT OF UKRAINE REGARDING THE CONSTITUTIONAL DUTIES OF A PERSON AND A CITIZEN - Anton Kazakov (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
The article analyzes the properties of the constitutional duties of a person and a citizen in the light of the legal positions of the Constitutional Court of Ukraine. After all, in order to renew the understanding of the legal nature, content orientation and social significance of the constitutional duties of a person and a citizen, it is necessary to analyze the understanding of this important category of jurisprudence through the prism of the legal positions of the Constitutional Court of Ukraine. The latter, due to their specific and meaningful content, as well as the authority of the body that formulates them, can be considered as original sources of the constitutional law of Ukraine. A careful analysis of the multifaceted practice of the Constitutional Court of Ukraine allowed to identify and analyze the basic legal positions, which in turn, supplementing and developing the achievements of the constitutional and legal doctrine of Ukraine from a practical point of view, indicate such properties of constitutional duties. First of all, all constitutional duties, regarding which the body of constitutional jurisdiction has formulated legal positions, are directly or indirectly related to ensuring the national security of Ukraine as a complex socio-legal category. Secondly, legal positions confirm the fact that constitutional duties are socially significant due to their special purpose and role in the life processes of society and the state. Thirdly, the Constitutional Court of Ukraine in its formulated legal positions emphasizes that the implementation of constitutional duties requires adequate guarantees from the state. Fourthly, in addition to the formalized guarantees, the body of constitutional jurisdiction indicated that the implementation of some constitutional duties requires public support and respect for the persons who implement them. Fifth, constitutional duties, giving rise to a wide variety of legal relations, are able to influence the relevant subjects and change, strengthen or fundamentally transform their legal status. Sixth, in some decisions, the Constitutional Court of Ukraine formulates legal positions that confirm the respective potential possibilities of constitutional obligations regarding their implementation in extraordinary situations, including those that require the introduction of a special period. And, finally, seventhly, the body of constitutional jurisdiction pointed out that the proper implementation of constitutional duties is aimed at neutralizing the factors that cause the need to introduce a special period.